2018
DOI: 10.1111/jssr.12496
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity Reduces Sexual Aggression and Coercion in a Longitudinal Cohort of College Men: Mediating Roles of Peer Norms, Promiscuity, and Pornography

Abstract: Extensive literature suggests that religiosity is a protective factor in reducing a number of deviant behaviors, including sexual aggression. Whereas previous research focused on the role of risky alcohol consumption in mediating the relationship between religiosity and sexual aggression, this study explores the hypothesized meditational paths from religiosity to sexual aggression and technology-based coercive behavior through peer norms, pornography consumption, and promiscuity. Findings from a four-year long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
0
13
1
Order By: Relevance
“…In contrast with previous studies among adolescents (Peter & Valkenburg, 2011;Vandenbosch, 2015) and adults (Hagen et al, 2018;Samueal L. Perry, 2017), we observed significant associations between the frequency of pornography use and panel attrition.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with previous studies among adolescents (Peter & Valkenburg, 2011;Vandenbosch, 2015) and adults (Hagen et al, 2018;Samueal L. Perry, 2017), we observed significant associations between the frequency of pornography use and panel attrition.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, dozens of research studies have examined the relationship between pornography consumption and aggressive behavior. Outcomes from these studies are mixed, yet those that find a relationship usually report small but statistically significant effects of pornography on aggressive behavior (Alexy et al, 2009;Burton et al, 2010) in mostly samples of male adolescent or college students (for two recent studies, see Dawson et al, 2019;Hagen et al, 2018). Other studies find no effects (Endrass et al, 2009;Hagan et al, 2018) or even inverse relationships (Diamond et al, 2011).…”
mentioning
confidence: 99%
“…Other studies find no effects (Endrass et al, 2009;Hagan et al, 2018) or even inverse relationships (Diamond et al, 2011). Further still, some studies suggest the relationship is more complex, citing both mediators and moderators that reduce the strength of the effect of pornography consumption on sexually aggressive behavior (Malamuth et al, 2000) or eliminate its influence altogether (Hagen et al, 2018;Kjellgren et al, 2009).…”
mentioning
confidence: 99%
“…A study using modified Iowa Gambling Task that included pornographic images reported that sexual arousal can interfere with feedback processing and decision making. 64 Sexual arousal has also shown to be associated with poorer performance in working memory and task switching. 58, 65 Moreover, studies have reported impairments in the ability to inhibit response to stimuli using go-no go tests.…”
Section: Neurobiology Of Addictionmentioning
confidence: 99%